Impact of Business Intelligence on Strategic Entrepreneurship: The Mediating Role of Organizational Agility - Al AQasrawi, Isra Sitan; Alafi, Khaled Khalaf (International Review of Management and Marketing, 2022)
The purpose of the study is to examine the impact of Business Intelligence (BI) on Strategic Entrepreneurship (SE) with the existence of Organizational Agility (OA) in Jordanian entrepreneurial companies. The researchers used the quantitative method, as it has an empirical nature. The questionnaire was adopted as a data collection tool. In total, 209 questionnaires were disturbed electronically among 16 entrepreneurial companies operating in King Hussein Business Park (KHBS) in Amman, Jordan. The analyzed results showed a high positive impact of BI on SE, which is seen evident in the results where BI dimensions (data warehousing, data mining, and On-Line Analytic Processing (OLAP)), have a statistically significant impact on SE and its dimensions (entrepreneurial mindset, applying creativity & developing innovation, opportunities identification, and acceptance of risk). Additionally, OA depicted a partial mediation between BI and SE. Furthermore, all main and sub hypotheses were significant and accepted, since the p-value of each analysis is less than 0.05. Finally, the researchers recommend applying BI in entrepreneurial companies that do not adopt it, and it should be given a high priority as it has been proven that BI increases the chances of identifying opportunities, accepting risks, and, moreover, developing innovative projects.